Andean women's distress narratives - Anderson, Jeanine (2000)
Promoting health and prolonging life are among the most cherished values ​​of any human society. Such universality contrasts, however, with how relative the multiple ways of understanding health and disease are. The differences begin with the classification of the ailments, the recognition of the symptoms and the association between these and the different pathological categories. They permeate the meaning of "being sick", the body-mind relationship (if any separation is recognized), the influence of the social world on people's perception of well-being, and even the influence of spiritual beings and supernatural forces.